Black Boxes - Versiegelungskontexte und Öffnungsversuche Interdisziplinäre Perspektiven - Geitz, Eckhard; Vater, Christian; Zimmer-Merkle, Silke (Materiale Textkulturen, 2020)
We are surrounded by complex things that affect us but which remain concealed behind interfaces. Examples of such black boxes are diverse: smart watches, artificial intelligence, complex software, and gene-editing technology. This interdisciplinary volume explores case examples of black boxes using theoretical analytic tools, looks at the ways they are sealed, and presents attempts to disclose their contents.